Socialization of Ranperda on Organization of Legal Aid to Poor Communities - Ichsan, Nursyamsi; Hasmiati Attas, Nasrah; Nasir, Citra (Cendekiawan Indonesia Timur, 2022)
Legal Aid is legal services provided by Legal Aid Providers free of charge to Legal Aid Recipients. The law is felt to be a frightening specter for underprivileged communities. Apart from general law with various complex problems, obtaining legal aid services is expensive. Because the profession of an advocate as a provider of legal services requires special education and expertise, the pay is also no joke. It is not surprising that many people still think twice when they want to ask for legal services, especially for economically disadvantaged people. Even though every person with problems with the law has the right to receive legal assistance from the time of investigation until a court decision has permanent legal force, providing legal assistance is part of human rights. Thus, through this socialization, it can help and provide understanding for the community, especially the less fortunate; when it comes to legal cases, they can find out that there is a plan to draft regional regulations regarding providing legal Aid for people experiencing poverty.